270 INCIDENCE OF CANCER IS INCREASED IN PATIENTS WITH PROGRESSIVE SYSTEMIC SCLEROSIS: A CASE CONTROL STUDY IN HALF A MILLION VETERANS. (1st January 2005) - Khurana, R.; Wolf, R. E.; Hayat, S.; Caldito, G. C.; Berney, S. M.
Abstract : Objective: To investigate the association of progressive systemic sclerosis (PSS) with cancer in the veteran population. Background: Previous studies have suggested an increased risk of cancer among patients with PSS. Methods and Materials: A retrospective cross sectional case control study was conducted using data from the VSN 16 VA database from 1998 to 2004. Multivariate logistic regression analysis was done to adjust for covariates including smoking, age, race, and gender. Statistical tests were conducted at a 5% level of significance. Results: A total of 484, 226 veterans were studied, 203 (0.04%) of whom had PSS. The diagnosis of PSS was determined to have a significant association with the diagnosis of any cancer, lung and skin cancers. PSS patients have a risk of developing cancer at 1.61 times the risk of non-PSS patients. The risk for skin and lung cancers among PSS patients is respectively 1.82 and 2.35 times the risk among non-PSS patients. (table ) Discussion: This study shows a positive correlation between PSS and the incidence of cancer in the veteran population. It has been suggested that lung cancer in PSS may arise in previously damaged or fibrotic lung. Our data should be evaluated with caution, given the limitations of the population, the database, and this being a case control study. However, the large size of the database was felt to limit the effect of these factors. Conclusion: Patients with PSS have an increased incidence of cancer in general and lung and skin cancer in particular.